Peran Literasi Keuangan Syariah dalam Meningkatkan Kesejahteraan Masyarakat: Studi Literatur - Tyara Ramadhani; Fanesa Lukman Putri; Eka Paramita; M. Abdul Majid; Irfan Saefuloh (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
The growth of finance in Indonesia hasn't matched the public’s understanding of it. This gap limits the use of financial products and services. As a result, its impact on improving peoples’ lives is still limited Most research focuses on measuring how much people know about finance or looks at relationships between variables. However, studies that combine findings about finance knowledge and its role in improving lives are scarce. This study aims to analyse how Islamic finance knowledge helps improve community welfare. It reviews articles from 2020 to 2025 on Google Scholar, Scopus, ScienceDirect, SpringerLink, Dimensions and Garuda. The study finds that Islamic finance knowledge helps people manage money better. It also leads to productive and responsible financial habits. Moreover, it expands finance inclusion and boosts community economic power. The impact of finance knowledge on well-being isn't always direct. It is influenced by behaviour and Islamic finance inclusion. Therefore, improving finance knowledge through education and collaboration between the government, schools and the Islamic finance industry is necessary. The use of financial products and services can be increased by improving Islamic finance knowledge. This can be done through education and outreach programs. The government, schools and the Islamic finance industry should work together to achieve this goal. Islamic finance knowledge plays a role in improving people’s lives. It helps people make financial decisions. This in turn can lead to financial stability and security. Improving finance knowledge is essential, for the growth of the Islamic finance sector. It can also help achieve inclusion and stability.